Autocad 2012 : a problem-solving approach - 401471 Tickoo, Sham (Clifton Park : Delmar, Cengage Learning, 2012)
Ch.1. Introduction to AutoCad -- Ch.2. Getting started with AutoCAD -- Ch.3. Starting with the Advanced sketching -- Ch.4. Working with drawing Aids -- Ch.5. Editing sketched objects-I -- Ch.6. Editing sketched object-II -- Ch.7. Creating text and tables -- Ch.8. Basic dimensioning, geometric dimensioning, and tolerancing -- Ch.9. Editing dimensions -- Ch.10. Dimension styles, multileader styles, and system variables -- Ch.11. Adding constraints to sketches -- Ch.12. Technical drawing with AUTOCAD -- Ch.13. Isometric drawings -- Ch.14. Hatching drawings -- Ch.15. Model space viewports, paper space viewports, and layouts -- Ch.16. Plotting drawings -- Ch.17. Template drawings -- Ch.18. Working with blocks -- Ch.19. Defining block attributes -- Ch.20. Understanding external references -- Ch. 21.Working with advanced drawing options -- Ch. 22. Grouping and advanced editing of sketches objects -- Ch. 23. Working with data exchange & object linking and embedding -- Ch. 24. THe user coordinate system -- Ch. 25. Getting started with 3D -- Ch. 26. Creating solid models -- Ch. 27. Modifying 3D objects -- Ch. 28. Editing 3D objects -- Ch. 29. Surface modeling -- Ch. 30. Mesh modeling -- Ch. 31. Rendering and animating design -- Ch. 32. AutoCAD on internet -- Ch. 33. Accessing external database -- Ch. 34. Script files and slide shows -- Ch. 35. Creating linetypes and hatch patterns -- Ch. 36. Customizing the acad.pgp file